Spatial revolute joints with clearance and friction for dynamic analysis of multibody mechanical systems - Marques, Pedro Filipe Lima (2016)
A study on the effects of dry spatial revolute joints with clearance and friction is delivered through this work. Both radial and axial clearances are taken into consideration which makes the model more realistic for three-dimensional motion. The kinematics of the contact between the journal and bearing are assessed, and used to evaluate the intra-joint normal and tangential contact forces. Moreover, a spatial slider-crank mechanism is used as an application example. The ideal case, the frictionless clearance joint and the joint with clearance and friction were compared, and the results show that clearance and friction have a significant impact in the dynamic response of the mechanical system.